Introduction to Aquaponic System - Mohammad Bodrul, Munir (UNISSA Press, 2024)
Nowadays, awareness on harmful substances that may occur in food products has increased. Thus, organic food has generated much interest among consumers, businesses and researchers. Some countries support organic farming through agricultural subsidy reform e.g. European Union. Many people are drawn into starting a small organic farm not only to practice healthy eating and lead a better-quality life, but also for the care of the environment. Organic production and marketing have grown at a fast pace and there is another alternative way of doing organic, which is by practicing aquaponics. Aquaponic is a farming system consisting of two combined farming, which are the rearing of aquatic animal and the growing of plants. This farming system has gained a lot of attention as it offers plenty of advantages including convenient farming, practicality, and applicability from small family-scale to commercial large-scale farming. The main objective of this book is to share the practical knowledge of basic aquaponic system. This book contains an introduction to the aquaponic system, an understanding of the principles practiced, the step-by-step construction of the aquaponic unit and also the approach to maintaining the system.